Crowdfunding of Entrepreneurial Projects in Sport - Ivan Novak; Blaženka Knežević; Petra Škrobot (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Dubrovnik, Croatia, 7-9 September 2017, 2017)
Crowdfunding, as a specific e-business activity, changes the way in which entrepreneurs collect money for financing their business projects in various business activities starting from social entrepreneurship and software development towards entertainment industry. No business activity is an exception to this trend. Due to its potential to influence and change traditional financial flows and to change traditional principles of financial intermediations, crowdfunding has drawn attention of scientists and practitioners who are trying to explain what could be consequences, risks, development phases and future trends in this field. In this paper, we give a theoretical insight into definitions, development and types of crowdfunding activity in general in the context of entrepreneurial self-financing. Then, on the basis of the case study analysis method, we outline several good practices of self-financing sports projects in developed markets in for each type of crowdfunding.
Keywords: L86; L83; O35; 330; crowdfunding; e-business; self-financing; entrepreneurship; sport management; sport